Manajemen Lingkungan Sekolah untuk Mewujudkan Proses Pembelajaran yang Kondusif - Ruwaidah, Ai Ira Siti; Adriawan, Aura Nazwa Ar’zahra; Melisa, Dhea Citra; Fitriani, Feni; Hasanah, Syifa Atiatul; Prihantini, Prihantini (Indo-MathEdu Intellectuals Journal, 2025)
A conducive school environment is an important factor in supporting the effectiveness of the learning process. This research is based on the need for a holistic approach in school environment management, especially considering the challenges of globalization and digitalization in the 21st century education era. This research aims to explore the management of the school environment that can create a comfortable, safe, and productive learning atmosphere. This research was conducted using a qualitative research method based on literature review, which includes literature analysis from various reliable sources. The main source of this research is scientific articles published on the Google Scholar database. Data analysis is carried out qualitatively with the stages of data reduction, data presentation, and conclusion drawing. The findings show that the management of the physical environment, such as cleanliness, availability of facilities, and school layout, contributes greatly to student comfort. In addition, social aspects such as interpersonal relationships between teachers, students, and parents, as well as psychological aspects in the form of a sense of security and emotional support, also greatly affect student motivation and achievement. Collaboration between teachers, principals, students, and parents is necessary to create an optimal environment. These results provide important insights for educators to design sustainable and innovative school management strategies